A contribuição da obra "Sobrevivendo no Inferno" dos Racionais MC´s para o letramento racial crítico sob o viés da teoria crítica da raça - Abreu, Bia Santos de (2025)
This study aims to investigate the contribution of the work “Sobrevivendo no Inferno” by the group Racionais MC’s to Critical Racial Literacy, through the lens of Critical Race Theory. The specific objectives are to map patterns, recurring themes, and elements that raise racial issues; to understand how Sobrevivendo no Inferno fosters critical dialogues about social and cultural issues in the Brazilian context; and, finally, to establish connections between the book and Critical Race Theory concepts to identify aspects that activate Critical Racial Literacy. The chosen methodological approach is grounded in a qualitativeinterpretivist epistemology (Denzin; Lincoln, 2006; Moita Lopes, 1996), with a documentary and exploration data collection procedure (Bell; Waters, 2014; Gil, 2008) based on applied theoretical concepts. The theoretical-methodological framework is anchored in the dialogical conception of language and otherness developed by the Bakhtin Circle (Amorim, 2004; Bakhtin 2011, 2014, 2015; Volóchinov 2021); studies on race, racism, and the invention of Blackness (Almeida, 2019; Munanga, 2004; Quijano, 2005; Mbembe, 2014); Critical Race Theory; and Critical Racial Literacy (Cumming, 2011; Delgado; Stefancic, 2021; Harris, 2000; Ross, 2018; Hatch, 2015; Ferreira, Queiroz, 2018; Ferreira, 2015). For the study, three analytical parameters are proposed: Critical Race Theory, Critical Racial Literacy, and the discursive aspects of the work, constituted by indicators for the analysis of the corpus, resulting from a comparison between the research objectives and the mobilized theoretical framework. The results of the analysis reveal that the work *Sobrevivendo no Inferno* serves as a tool for denouncing racial inequalities in Brazil, in addition to being a resource for raising awareness and resistance as its narratives challenge hegemonic discourses and expose structural racism. Furthermore, the work highlights how structural racism operates in the periphery by addressing themes such as police violence, mass incarceration, the genocide of young Black people, social marginalization, and racial and economic inequality.” Analysis results reveal that the work Sobrevivendo no Inferno serves as a tool to denounce racial inequalities in Brazil, as well as a means of raising awareness and resistance when its narratives challenge dominant discourses and expose structural racism. Furthermore, the work demonstrates that structural racism operates in the periphery by addressing issues such as police violence, mass incarceration, the genocide of Black youth, social marginalization, and racial and economic inequality.